High porosity cyclotriphosphazene-based hyper-crosslinked polymers as efficient cationic dye MB adsorbents. (28th April 2022) - Xiong, Gang; Gao, Shan; Zhang, Qian; Ren, Baoyi; You, Lixin; Ding, Fu; He, Yongke; Sun, Yaguang
Abstract: Inspired by triptycene unit, the rigid paddle wheel compounds tris(o-phenylenedioxy)cyclotriphosphazene (TPP) and tris(2, 3-naphthalenedioxy)cyclotriphosphazene (TNP) were synthesized and employed as core building blocks to construct high porosity hyper-crosslinked polymers (HCP-TPP and HCP-TNP ) via Friedel-Crafts alkylation reaction with formaldehyde dimethyl acetal (FDA). The bulk of HCP-TPP and HCP-TNP were comprised of nano-particles and exhibited hierarchical pore structures with remarkable high BET specific surface area of 1641.9 and 1700.2 m 2  g −1, respectively. The adsorption capacities of HCP-TPP and HCP-TNP toward cationic dye methylene blue (MB) run up to 504.6 and 409.1 mg g −1 at 25 °C, respectively, but they hardly adsorbed anionic dye methyl orange (MO), exhibiting charge selectivity. The adsorption behaviors on MB were in consistence with the pseudo-second-order model and Langmuir model. The estimated thermodynamic parameters indicated the adsorption process was spontaneous and exothermic. Graphical abstract: Inspired by triptycene unit, the rigid paddle wheel compounds tris(o-phenylenedioxy)cyclotriphosphazene (TPP) and tris(2, 3-naphthalenedioxy)cyclotriphosphazene (TNP) were synthesized and employed as core building blocks to construct high porosity hyper-crosslinked polymers (HCP-TPP and HCP-TNP ) via Friedel-Crafts alkylation reaction with formaldehyde dimethyl acetal (FDA). The bulk of HCP-TPP and HCP-TNP were comprised of nano-particles and exhibited hierarchical pore structures with remarkable high BET specific surface area of 1641.9 and 1700.2 m 2  g −1, respectively. The adsorption capacities of HCP-TPP and HCP-TNP toward cationic dye methylene blue (MB) run up to 504.6 and 409.1 mg g −1 at 25 °C, respectively, but they hardly adsorbed anionic dye methyl orange (MO), exhibiting charge selectivity. The adsorption behaviors on MB were in consistence with the pseudo-second-order model and Langmuir model. The estimated thermodynamic parameters indicated the adsorption process was spontaneous and exothermic. Image 1 Highlights: Two novel cyclotriphosphazene-based hyper-crosslinked polymers were prepared from low cost raw materials. They exhibited hierarchical structures with the highest BET specific surface areas among cyclotriphosphazene -based porous materials. They charge-selectively absorbed cationic dye methylene blue (MB) with absorption capacities of 504.6 and 409.1 mg g −1 at 25 °C.